Paternas literas confirmamus: Il libro dei privilegi e delle facoltà del mastro portolano di Terra di Lavoro (secc. XV-XVII) Paternas literas confirmamus: The book of privileges and authority of the "mastro portolano" of Terra di Lavoro (15th-17th Centuries) - Giuliana Capriolo (Regna: Testi e studi su istituzioni, cultura e memoria del Mezzogiorno medievale, 2017)
Within the bureaucratic and fiscal system of the Reign of Naples a strategic role was played by the provincial office of the mastro portolano which was established in each of the twelve provinces of the Reign and conferred with royal privilege in order to preserve the public land. In particular, in Naples and in its province of Terra di Lavoro the Office of Portolania was conducted for two hundred years by some exponents of the noble Moccia family from the Neapolitan "Sedile di Portanova". Concerning this family, we have examined a little membrane code that at the moment is kept at the Archive of the Franciscan Convent of Baronissi. Some copies of royal and administrative documents, dating back to the Aragonese and to the Spanish Viceroy periods, are gathered in this book. They were registered at the Royal Chamber of the Sommaria or issued directly by the curia of the maestro portolano and in particular they certify some privileges and prerogatives that were granted to the Moccias as royal officers. The code constitutes an interesting example of "document in the form of a book" or as a "book-document" that represented not only the munimen in defense of acquired rights and privileges, but also carried out the task of "archive" and "storage".